Adolescent Suicides in the Western Pacific Region Have Become a More Serious Public Health Problem than in Other Regions - Ruri Okubo; Ryusuke Matsumoto; Eishi Motomura; Motohiro Okada (Psychiatry International)
Globally, suicide mortality rates have decreased in this century; however, it has been reported that the decreasing trends of some subgroups were attenuated in the late 2010s. These tendencies are pronounced among adolescents. In this study, the temporal fluctuations of the age-standardized death rate of suicide (ASDR-suicide), crude mortality rate of suicide (CMR-suicide), and percentage of suicides per total deaths (PTD-suicide) among adolescents (10–24 years) in the global high-income and middle-income countries and in the Western Pacific Region (WPR) from 1990 to 2019, as well as the fixed effects of communication factors (penetration of cellular telephones and the Internet) on the ASDR-suicide/CMR-suicide/PTD-suicide of adolescents, were analyzed using the WHO Mortality Database. The male ASDR-suicide in global middle-income countries decreased, and those of males in global high-income countries and females in middle-income countries were unchanged, while the rate of other groups (males in the WPR and females in high-income countries and the WPR) increased. The ASDR-suicide of adolescent males in the WPR was almost equivalent to that of males in global high-income and middle-income countries in the 1990s but was higher than the rate in the 2010s. The ASDR-suicide of adolescent females in the WPR was consistently higher than that of females in global high-income and middle-income countries from 1990 to 2019, but the differences widened over time. The PTD-suicide of both males and females in middle-income countries was unchanged, whereas the PTD-suicide in global high-income countries and the WPR increased over time. The PTD-suicide in the WPR markedly increased by >40% in the late 2010s. The fixed effects of cellular telephone and Internet penetrations were negatively and positively related to adolescent suicide in the WPR, respectively. Therefore, these results suggest that, in this century, suicide prevention in adolescent health activities has been increasing in importance in the WPR compared with other regions.